The Influence of the Anchored Instruction (AI) Model on Students' Mathematical Problem Solving Ability - Simbolon, Asep; Gita Rani Putri Mangiri; Dadan Dasari (LPPM Universitas Advent Indonesia, 2024)
Problem-solving is one of the mathematical skills every student must possess in mathematics learning. Therefore, teachers had to be adept at selecting a learning model that could enhance students' mathematical problem-solving skills. One learning model that could enhance students' mathematical problem-solving skills was the Anchored Instruction learning model. This research aimed to determine the influence of the Anchored Instruction learning model compared to conventional learning on students' mathematical problem-solving abilities. The research method was quasi-experimental, where the experimental group utilized the Anchored Instruction learning model, while the control group utilized conventional learning. The results from this research indicated that students' mathematical problem-solving abilities taught using the Anchored Instruction learning model were higher than those taught using conventional learning.